Penanaman Nilai-Nilai Karakter Melalui Kegiatan Storytelling dengan Menggunakan Cerita Rakyat Sasak - Aisyah Amatul Qayyum (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2025)
This study aims to analyze the application of storytelling method based on Sasak folklore to instill character values in children. The research used is qualitative research. The type of approach used is a qualitative descriptive approach. Data collection techniques are observation, interview, and documentation. The data collection instruments used are researchers, observation sheets, and interviews. Data validity test with credibility test, transferability test, dependability and confirmability. The data analysis process was carried out using the Miles & Huberman interactive analysis model, namely Data Collection, Data Display, Data Reduction, and Conclusion Drawing The results of the study found that storytelling activities using folklore were able to instill character values. The character values that emerged included the characters of responsibility, independence, honesty, religion, and cooperation. The characters that emerged were an accumulation that emerged from the children's behavior after listening to the folktales used such as “lelampaq Lendong Kaoq” and “Tegodek-godek and Tetunteltuntel”.